Study on the Heat Treatment Process of High Strength-toughness Automobile Chain Roller - Yang Weiming; Xing Jianheng; Lu Xudong (Jixie chuandong, 2016)
The organization and performance of 20 CrNiMo automobile chain roller after the heat treatment of carburizing and quenching + low tempering,carburizing and quenching + medium- temperature tempering and carburizing and quenching + isothermal salt bath heat treatment are studied. The carburizing and quenching + salt bath isothermal heat treatment is the best heat treatment process for automobile chain roller is determined. Comparing with the conventional quenching + low tempering temperature strength σb increased by15.2%,the plasticity increased by 60%,the toughness increased by 80%. The whole chain rotary fatigue performance increased by 3.2 times.